2017
DOI: 10.1093/jac/dkw576
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasmid-borne oqxAB on the development of fluoroquinolone resistance and bacterial fitness in Escherichia coli

Abstract: The possession of plasmid-borne oqxAB may facilitate the evolution of fluoroquinolone resistance, and the fitness cost of OqxAB-encoding plasmids could be compensated by additional chromosomal mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In addition to chromosomally-encoded efflux pumps, the presence of plasmid-encoded efflux pump genes oqxAB and qepA has been shown to increase ciprofloxacin MIC in E. coli . 34,35 oqxAB confers a median fold increase in MIC of 7.5 (range 2-16x fold increase) 35, 6264 , while qepA confers a median fold increase of 4.5 (range 2-31x fold increase, Table 2). 34,52,65–68…”
Section: Resultsmentioning
confidence: 99%
“…In addition to chromosomally-encoded efflux pumps, the presence of plasmid-encoded efflux pump genes oqxAB and qepA has been shown to increase ciprofloxacin MIC in E. coli . 34,35 oqxAB confers a median fold increase in MIC of 7.5 (range 2-16x fold increase) 35, 6264 , while qepA confers a median fold increase of 4.5 (range 2-31x fold increase, Table 2). 34,52,65–68…”
Section: Resultsmentioning
confidence: 99%
“…This is the first report of the coexistence of three PMQR genes on a multiple resistance plasmid. Studies showed that PMQR was usually low level, and its MIC value was below the CLSI resistance breakpoint [21]. The MIC of c749 demonstrated intermediate resistance, which indicated that the coexistence of three PMQR genes can cause an increase in MIC more than the presence of one or two PMQR genes reported [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…The stability of the mcr-1 –positive plasmids was investigated in vitro according to a previously described protocol (Bryksin and Matsumura, 2010 ; Wang et al, 2017 ). In brief, transconjugants E. coli DH5α/pHNSHP45, E. coli DH5α/pHNSHP45-2, E. coli DH5α/pHNSHP23, E. coli DH5α/pHNSHP17, and E. coli DH5α/ pHNSHP24 were propagated by serial transfer for 14 days of passage.…”
Section: Methodsmentioning
confidence: 99%